Fractionated low-dose exposure to ionizing radiation leads to DNA damage, epigenetic dysregulation, and behavioral impairment. Issue 4 (31st January 2017) - Koturbash, Igor; Jadavji, Nafisa M.; Kutanzi, Kristy; Rodriguez-Juarez, Rocio; Kogosov, Dmitry; Metz, Gerlinde A.S.; Kovalchuk, Olga
Abstract : Studies of F ractionated E xposure to L ow D oses of I onizing R adiation (FELDIR) has become of increasing importance to clinical interventions. Its consequences on DNA damage, physical, and mental health have been insufficiently investigated, however. The goal of this study was to determine the effects of FELDIR on the brain using a mouse model. We addressed the levels of DNA damage, global genomic methylation, and DNA methylation machinery in cerebellum, frontal lobe, olfactory bulb and hippocampal tissues, as well as behavioral changes linked to FELDIR exposure. The results reveal increased levels of DNA damage, as reflected by increased occurrence of DNA S trand B reaks (SBs) and dysregulation of stress-response kinase p38. FELDIR also resulted in initial loss of global genomic methylation and altered expression of methyltransferases DNMT1 (down-regulation) and DNMT3a (up-regulation), as well as methyl-binding protein MeCP2 (up-regulation). FELDIR-associated behavioral changes included impaired skilled limb placement on a ladder rung task, increased rearing activity in an open field, and elevated anxiety-like behaviors. The said alterations showed significant dose and tissue specificity. Thus, FELDIR represents a critical impact on DNA integrity and behavioral outcomes that need to be considered in the design of clinical intervention studies.